Purinergic signaling during Porphyromonas gingivalis infection - Almeida-da-Silva, Cássio Luiz Coutinho (Biomed J, 2016)
Despite recent advances unraveling mechanisms of host–pathogen interactions in innate immunity, the participation of purinergic signaling in infection-driven inflammation remains an emerging research field with many unanswered questions. As one of the most-studied oral pathogens, Porphyromonas gingivalis is considered as a keystone pathogen with a central role in development of periodontal disease. This pathogen needs to evade immune-mediated defense mechanisms and tolerate inflammation in order to survive in the host. In this review, we summarize evidence showing that purinergic signaling modulates P. gingivalis survival and cellular immune responses, and discuss the role played by inflammasome activation and cell death during P. gingivalis infection.